Optimizing the digital customer journey—Improving user experience by exploiting emotions, personas and situations for individualized user interface adaptations - Christian Märtin; Bärbel Christine Bissinger; Pietro Asta (Journal of Consumer Behaviour, 2021)
This paper discusses a novel approach for exploiting emotions and situation-aware software adaptation methods for individualizing some of the touch points of the digital customer journey and thereby optimizing customer experience and effectiveness of e-commerce applications. Our approach uses emotion recognition, eye-tracking, and other individual tracking methods as well as customer personas for adapting interactive web applications by accessing a flexible adaptation framework at runtime. The framework allows for individualization at runtime by applying situation-aware adaptations. Two experimental customer studies were carried out in the e-commerce domain in order to provide a basis for exploitable emotion- and persona-related situational changes. The results of the studies were used to demonstrate the potential of our situation analytic adaptation approach with examples from a commercial beauty-products e-business portal.
Keywords: 320